Single-cell RNA-seq reveals FGF12 as a prognostic biomarker in low-grade endometrial stromal sarcoma - Miao, Yu; Dong, Meng; Zhou, Qiyin; Thiel, Julia; Li, Na; Cai, Ying; Yuan, Dan; Wang, Haitao; Jin, Su-Han; Yang, Hua; Wang, Jinjing; Frey, Benjamin; et al. (Frontiers in Immunology, 2024)
BackgroundLow-grade endometrial stromal sarcoma (LG-ESS) is a rare uterine malignancy characterized by its complex tumor microenvironment (TME) and high recurrence rates, posing challenges to accurate prognosis and effective treatment. Identifying prognostic biomarkers is essential for improving patient stratification and guiding therapeutic strategies.MethodsUsing single-cell transcriptome analysis combined with H&E and multiplex immunofluorescence staining, we identified a subpopulation of tumor cells in LG-ESS and further validated the association of this subpopulation and its characteristic genes with LG-ESS prognosis by molecular characterization and bulk transcriptome data.ResultsOur analysis reveals multiple cellular subpopulations within the tumor tissue, particularly a tumor cell subpopulation among them which is associated with poor prognosis. Originating from normal stromal fibroblasts, this subpopulation appears to play a crucial role in TME remodeling, smooth muscle cell behavior, and potentially in tumorigenesis and metastasis. Of particular interest in this subpopulation is the highly expressed FGF12 gene, which is significantly associated with a shortened survival in ESS, highlighting its potential as a prognostic biomarker.ConclusionOur study reveals the complexity of TME within the LG-ESS and highlights the role that tumor cell subpopulations play in disease progression and patient prognosis. The identification of FGF12 as a prognostic biomarker suggests a new approach for the personalized treatment and prognosis monitoring of patients.